A note on the space of fuzzy measurable functions for a monotone measure - Wu, Chong; Ren, Xuekun; Wu, Congxin (Fuzzy sets and systems, 2011)
In this paper, we give a necessary and sufficient condition to guarantee that the space of all finite measurable functions for a monotonic measure is a topological vector space with a countable local base and in this space convergence with respect to this topology is equivalent to the convergence in measure.